Key aspects of underground hydrogen storage in depleted hydrocarbon reservoirs and saline aquifers: A review and understanding - Sadkhan, Rawaa A.; Al-Mudhafar, Watheq J. (Energy Geoscience, 2024)
Underground hydrogen storage is critical for renewable energy integration and sustainability. Saline aquifers and depleted oil and gas reservoirs represent viable large-scale hydrogen storage solutions due to their capacity and availability. This paper provides a comparative analysis of the current status of hydrogen storage in various environments. Additionally, it assesses the geological compatibility, capacity, and security of these storage environments with minimal leakage and degradation. An in-depth analysis was also conducted on the economic and environmental issues that impact the hydrogen storage. In addition, the capacity of these structures was also clarified, and it is similar to storing carbon dioxide, except for the cushion gas that is injected with hydrogen to provide pressure when withdrawing from the store to increase demand. This research also discusses the pros and cons of hydrogen storage in saline aquifers and depleted oil and gas reservoirs. Advantages include numerous storage sites, compatibility with existing infrastructure, and the possibility to repurpose declining oil and gas assets. Specifically, it was identified that depleted gas reservoirs are better for hydrogen gas storage than depleted oil reservoirs because hydrogen gas may interact with the oil. The saline aquifers rank third because of uncertainty, limited capacity, construction and injection costs. The properties that affect the hydrogen injection process were also discussed in terms of solid, fluid, and solid-fluid properties. In all structures, successful implementation requires characterizing sites, monitoring and managing risks, and designing efficient storage methods. The findings expand hydrogen storage technology and enable a renewable energy-based energy system. [Display omitted] •A fundamental review of H2 storage in depleted hydrocarbon reservoirs and saline aquifers.•A comparative discussion of the potential underground environments for H2 storage.•The selection criteria for suitable H2 storage sites.•The influential parameters on controlling the H2 storage.•An illustration of the rock-fluid interaction through the H2 storage.